Effects of serotonin 2A/1A receptor stimulation on social exclusion processing - Preller, Katrin H. (Proc Natl Acad Sci U S A, 2016)
Social ties are crucial for physical and mental health. However, psychiatric patients frequently encounter social rejection. Moreover, an increased reactivity to social exclusion influences the development, progression, and treatment of various psychiatric disorders. Nevertheless, the neuromodulatory substrates of rejection experiences are largely unknown. The preferential serotonin (5-HT) 2A/1A receptor agonist, psilocybin (Psi), reduces the processing of negative stimuli, but whether 5-HT2A/1A receptor stimulation modulates the processing of negative social interactions remains unclear. Therefore, this double-blind, randomized, counterbalanced, cross-over study assessed the neural response to social exclusion after the acute administration of Psi (0.215 mg/kg) or placebo (Pla) in 21 healthy volunteers by using functional magnetic resonance imaging (fMRI) and resting-state magnetic resonance spectroscopy (MRS). Participants reported a reduced feeling of social exclusion after Psi vs. Pla administration, and the neural response to social exclusion was decreased in the dorsal anterior cingulate cortex (dACC) and the middle frontal gyrus, key regions for social pain processing. The reduced neural response in the dACC was significantly correlated with Psi-induced changes in self-processing and decreased aspartate (Asp) content. In conclusion, 5-HT2A/1A receptor stimulation with psilocybin seems to reduce social pain processing in association with changes in self-experience. These findings may be relevant to the normalization of negative social interaction processing in psychiatric disorders characterized by increased rejection sensitivity. The current results also emphasize the importance of 5-HT2A/1A receptor subtypes and the Asp system in the control of social functioning, and as prospective targets in the treatment of sociocognitive impairments in psychiatric illnesses.